2018
DOI: 10.1103/physrevapplied.9.044035
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Magnetostriction of CoFe2O4 and Its Role in Magnetoelectric Composites

Abstract: Applications of magnetostrictive materials commonly involve the use of the dynamic deformation, i.e., the piezomagnetic effect. Usually, this effect is described by the strain derivative ∂λ=∂H, which is deduced from the quasistatic magnetostrictive curve. However, the strain derivative might not be accurate to describe dynamic deformation in semihard materials as cobalt ferrite (CFO). To highlight this issue, dynamic magnetostriction measurements of cobalt ferrite are performed and compared with the strain der… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
23
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(25 citation statements)
references
References 87 publications
(101 reference statements)
2
23
0
Order By: Relevance
“…It has been recently shown the strain derivative calculated from strain-field curves so obtained is not the appropriate parameter to describe dynamic deformation under alternate driving for semi-hard materials such as cobalt ferrite. 50 Instead, effective piezomagnetic coefficients directly obtained from dynamic magnetostriction measurements, which are consistently lower than quasistatic ones, must be used to calculate ME coefficients, as shown in Ref. 50.…”
Section: Potential For Me Composites: Analytical Calculationsmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been recently shown the strain derivative calculated from strain-field curves so obtained is not the appropriate parameter to describe dynamic deformation under alternate driving for semi-hard materials such as cobalt ferrite. 50 Instead, effective piezomagnetic coefficients directly obtained from dynamic magnetostriction measurements, which are consistently lower than quasistatic ones, must be used to calculate ME coefficients, as shown in Ref. 50.…”
Section: Potential For Me Composites: Analytical Calculationsmentioning
confidence: 99%
“…50 Instead, effective piezomagnetic coefficients directly obtained from dynamic magnetostriction measurements, which are consistently lower than quasistatic ones, must be used to calculate ME coefficients, as shown in Ref. 50. Dynamic piezomagnetic coefficients can reach up to 70 % of the quasistatic ones under optimized ac and bias magnetic fields.…”
Section: Potential For Me Composites: Analytical Calculationsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, for most of these applications, the key feature is not the static magnetostriction but the dynamic one, also known as piezomagnetic effect. Strictly speaking, the piezomagnetic coefficient is defined as the strain oscillation induced by an alternating magnetic field H AC at any bias field H DC [1], [7], [8], which can be written:…”
Section: Introductionmentioning
confidence: 99%
“…We have recently shown that this approximation may lead into quite relevant errors when evaluaiting ME devices performances particularly when semi-hard magnetostrictive materials (e.g. cobalt ferrites) are involved [8]. In fact, the strain derivative depends on the differential susceptibility χ dif f whereas the piezomagnetic effect arises from the dynamic susceptibility χ AC at any bias field.…”
Section: Introductionmentioning
confidence: 99%